Pengaruh Motivasi Terhadap Kinerja Tenaga Rekam Medis - Andi Yusuf; Muhammad Syafar; Rosmasrah Rosmasrah; Hasmah Hasmah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; Medical records are files containing records and documents about patients that contain identity, examination, treatment, and other medical actions. Aim; determine the effect of motivation on the performance of medical record personnel, incentives, working conditions, physical activity, work performance, responsibilities. Method; The type of research used is an analytical survey method with a cross-sectional study approach. The population in this study were all medical record personnel with a total sample of 46 respondents. Results; shows that there is a relationship between giving incentives (p = 0.018), work responsibilities (p = 0.031), and physical activity (p = 0.011) on the performance of medical record personnel while there is no relationship between working conditions (p = 0.501) and work performance (p = 0.417) on the performance of medical record personnel. Conclusion; that there is a relationship between the provision of incentives, physical activity, responsibility for the performance of medical records, and there is no relationship between working conditions, work performance on the performance of medical record personnel.